The effect of vinboron on the expression processes of apoptosis in gastric mucosa with ibuprofen-induced gastropathy in rats - Гладких, Ф.В.; Степанюк, Н.Г.; Сокирко, М.В. (Abstracts of the ІХ-th International Interdisciplinary Scientific Conference of Young Scientists and medical students «Actual problems of clinical and theoretical medicine» (International Scientific Interdisciplinary Conference – ISIC: abstracts (May 19–20, 2016). Kharkiv, 2016. P. 18–19., 2016)
The effect of vinboron on the expression processes of apoptosis in gastric mucosa with ibuprofen-induced gastropathy in rats
Hladkykh F. V., Stepaniuk N. H., Sokyrko M. V. The effect of vinboron on the expression processes of apoptosis in gastric mucosa with ibuprofen-induced gastropathy in rats. Abstracts of the ІХ-th International Interdisciplinary Scientific Conference of Young Scientists and medical students «Actual problems of clinical and theoretical medicine» (International Scientific Interdisciplinary Conference – ISIC: abstracts (May 19–20, 2016). Kharkiv, 2016. P. 18–19.
Keywords: ibuprofen; gastric mucosa; vinboron; gastropathy